Emergency Medicine and the Role It Plays in Public Health: Monitoring for Measles Outbreaks in the Emergency Room - Ismail , Lubna (SciWise, 2025)
Interview of Katie Mattina an Emergency Physician practicing in Hamilton, Ontario. Dr. Mattina completed her undergraduate education at McGill University, medical school at the University of Toronto and her Family Medicine-Emergency Medicine residency at McMaster University